Relationship between the Eruption Time of First Primary Tooth and Developmental Parameters in Infants Aged 2-15 Months - Kooshki, Fahimeh; Kamareh, Sanaz; Mighani, Fatemeh; Mohamadian, Fatemeh (Journal of Dental School, 2024)
Objectives One of the important indicators of growth and development is tooth eruption timing, which is influenced by various genetic and environmental factors. This study aimed to assess the relationship between different developmental parameters and eruption time of first primary tooth in infants aged 2-15 months. Methods This cohort study was conducted on 873 infants aged 2-15 months in eastern health centers of Tehran, Iran. The height, weight, head circumference, breastfeeding/bottle-feeding practices, vitamin AD supplementation, and maternal age at birth of the infants were recorded. The eruption time of first primary tooth was recorded by monthly examination of infants at the health centers. The effects of qualitative and quantitative variables were analyzed using the independent t-test and Chi-square test, respectively. Linear regression analysis was performed to investigate the simultaneous effects of growth parameters on tooth eruption time at a significance level of 0.05. Results The eruption time of first primary tooth had an inverse relationship with the weight (P<0.001), height (P=0.003), and head circumference (P=0.01) of the infants. The mean eruption time of the first primary tooth was 7.6 ± 1.7 months in normal birth weight infants (above 2500 g) and 9.7 ± 1.9 months in low birth weight infants (below 2500 g). There was no significant correlation between gender and the eruption time of the first primary tooth (P=0.16). However, the eruption time had significant relationships with maternal age, breastfeeding, and vitamin AD supplementation (P=0.001). Conclusion higher birth weight, height, and head circumference, as well as breastfeeding and receiving vitamin AD supplements are correlated with earlier eruption of first primary tooth.